Apk Codez (E-Modul): Perancangan Apk Edukasi untuk Siswa RPL - Fadhlirrahman Baso; Ekha Mustika Putri; Sulfan Ardiansyah; Juan Veron Ibrani (Sakura Digital Nusantara, 2024)
The rapid advancement of digital technology has increased the demand for programming skills across various industries. Formal education often falls short in providing the specific and current technological skills required. Therefore, students need additional learning platforms to develop their abilities independently and systematically. CodeZ, an APK-based application, addresses this need by offering courses in various programming languages, enabling students to learn new skills progressively. Using the ADDIE model, the development of this interactive module ensures a systematic approach comprising Analysis, Design, Development, Implementation, and Evaluation stages. Research results show that the CodeZ application is effective in aiding students, particularly SMK RPL students, in learning programming skills through practical exercises, discussion forums, and mentor support. Feedback indicates improved understanding and application of programming concepts, making the learning process enjoyable and practical. Future research should expand the scope of materials, enhance interactivity, develop personalization features, establish industry partnerships, and conduct ongoing evaluations to maintain the application's relevance and effectiveness.